Effect of interaction of nitrogen and phosphorus on seed and essential oil yield of ajowan (Trachyspermum ammi L.) genotypes - Madalageri, V Krishnamoorthy, M B (Journal of Spices and Aromatic Crops, 2000)
Field experiments conducted at Dharwad (Kamataka, India), to study the effect of interaction of nitrogen and phosphorus on seed yield and essential oil yield of ajowan (Trachyspermum ammi) genotypes, revealed that number of tertiary branches increased significantly with increasing levels of interaction of phosphorus and nitrogen in the genotypes BEN-l and BEN-2. The number of umbels increased significantly with increasing levels of phosphorus and nitrogen combinations. Significantly higher number of seeds was recorded in BEN-l at P50 + N100 and at P50 + N25 in BEN-2. Thousand seed weight significantly decreased in BEN-l with increasing levels of phosphorus and nitrogen combination, whereas in BEN-2 it increased with increasing levels of phosphorus and nitrogen combinations. Seed yields were signifiantly higher at P50 + N100 in BEN-l (20.50 q ha-1) and BEN-2 (14.61 q ha-1), respectively. Essential oil yields were significantly higher at P50 + N100 in BEN-l (82.04 kg ha-1) and BEN-2 (26.30 kg ha-1), respectively.